Moral Dilemmas in the Work of Yury Trifonov - Richard Chapple (Studies in 20th & 21st Century Literature, 1989)
The work of soviet novelist and playwright Yury Trifonov displayed throughout a concern with moral dilemmas and ethical choice. What distinguished the writing after 1969 from the earlier production was a shift away from facile platitudes of socialist dogma to a vision that would account more fully for the moral ambiguity with which modern life confronts the individual.
Keywords: soviet novelist; Yury Trifonov; moral dilemmas; ethical choice; 1969; socialist dogma; socialist; moral ambiguity; modern life; individual